Copy number variation sequencing‐based prenatal diagnosis using cell‐free fetal DNA in amniotic fluid. (17th May 2016) - Qi, Qingwei; Lu, Sijia; Zhou, Xiya; Yao, Fengxia; Hao, Na; Yin, Guangjun; Li, Wenhui; Bai, Junjie; Li, Ning; Cram, David S.
Abstract: Objective: The study aimed to determine whether cell‐free fetal DNA (cffDNA) present in amniotic fluid supernatant can be used as a surrogate for amniocyte‐based diagnosis of fetal chromosomal abnormalities. Method: Amniocentesis was performed on 28 high‐risk pregnancies. Amniocytes and the cffDNA fraction were prepared from the amniotic fluid samples. Chromosomal analysis of amniocytes was performed by either karyotyping or single nucleotide polymorphism (SNP) arrays. The corresponding cffDNA samples were blindly analyzed by copy number variation (CNV) sequencing in an independent laboratory. Results: In the 28 matching amniocyte and cffDNA samples, there was a high diagnostic concordance for detection of euploidy, aneuploidy and CNVs. From ten samples referred for karyotyping, two aneuploidies (20%) were identified. From 18 samples referred for SNP array analysis, three pathogenic CNVs (16.7%) were identified. CNV sequencing of the 28 cffDNA samples also detected the two aneuploidies and the three pathogenic CNVs, giving an overall concordance rate of 100% for detection of pathogenic chromosome abnormalities. Compared with SNP array analysis, CNV sequencing returned a higher yield of benign or variants of unknown significance. Conclusion: Copy number variation sequencing of cffDNA represents an alternative approach to conventional prenatal diagnostic methods for reliable and accurate detection of clinically significant chromosomal abnormalities. © 2016 John Wiley & Sons, Ltd. Abstract : What's Already Known About This Topic? Amniotic fluid is a source of amniocytes for traditional prenatal genetic diagnosis. Discarded amniotic fluid contains cell‐free fetal DNA. What Does This Study Add? Direct sequencing of cell‐free fetal DNA in amniotic fluid supernatant represents a promising alternative approach for prenatal diagnosis of fetal chromosome abnormalities where traditional amniocyte‐based diagnosis fails.